2004
DOI: 10.1111/j.1460-9568.2004.03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding partners L1 cell adhesion molecule and the ezrin‐radixin‐moesin (ERM) proteins are involved in development and the regenerative response to injury of hippocampal and cortical neurons

Abstract: Regeneration of the adult central nervous system may require recapitulation of developmental events and therefore involve the re-expression of developmentally significant proteins. We have investigated whether the L1 cell adhesion molecule, and its binding partner, the ezrin-radixin-moesin (ERM) proteins are involved in the neuronal regenerative response to injury. Hippocampal and cortical neurons were cultured in vitro on either an L1 substrate or poly-L-lysine, and ERM and other neuronal proteins were locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 46 publications
(51 reference statements)
1
44
0
Order By: Relevance
“…Previous studies have shown that ERM proteins are essential for neuronal morphogenesis and growth cone motility (Paglini et al, 1998;Castelo and Jay, 1999). In hippocampal neurons, ERM proteins were localized to growth cones and colocalized with L1 Haas et al, 2004). We have observed similar colocalization of activated ERMs and L1 in growth cones of cerebellar neurons (supplemental Fig.…”
Section: L1-mediated Branching Requires Interactions With Erm Proteinssupporting
confidence: 69%
“…Previous studies have shown that ERM proteins are essential for neuronal morphogenesis and growth cone motility (Paglini et al, 1998;Castelo and Jay, 1999). In hippocampal neurons, ERM proteins were localized to growth cones and colocalized with L1 Haas et al, 2004). We have observed similar colocalization of activated ERMs and L1 in growth cones of cerebellar neurons (supplemental Fig.…”
Section: L1-mediated Branching Requires Interactions With Erm Proteinssupporting
confidence: 69%
“…A functional binding between L1, an axonal adhesion molecule belonging to the Ig superfamily, and ERM proteins is involved in neurite branching during development and regenerative response to injury (Dickson et al, 2002;Haas et al, 2004;Cheng et al, 2005). In axonal growth cones, radixin and moesin regulate their morphology and motility (Paglini et al, 1998;Castelo and Jay, 1999).…”
Section: Erm Proteins In Dendritic Filopodiamentioning
confidence: 99%
“…Dunican and Doherty (36) suggest that when N-CAM, L1, or N-cadherin on a growth cone binds a suitable ligand, clustering and activation of FGF receptors leads to phosphorylation of GAP-43 and, as a result, to neurite outgrowth-promoting changes in the actin cytoskeleton. Thus, although the neurite growth-promoting effect of CAMs may be mediated by multiple intracellular signal transduction pathways (16,37,40), the Dunican and Doherty model would explain why coexpression of L1 and GAP-43 by neurons is associated with greater axon sprouting than occurs with the expression of either L1 or GAP-43 alone.…”
Section: Discussionmentioning
confidence: 99%
“…Its effects are mediated by homophilic binding to L1 or heterophilic binding to ligands, including integrins, on other cells, or by binding to extracellular matrix-associated molecules, including chondroitin sulfate proteoglycans, neurocan, and phosphacan (15). The intracellular domain of L1 binds to ezrin-radixinmoesin membrane-cytoskeleton linker proteins that are involved in growth cone morphology and motility and second messenger pathways (16,17). L1 also interacts with FGF receptors, and L1-induced neurite outgrowth requires the tyrosine kinase activity of FGF receptors to activate intracellular signaling cascades, including Ras͞mitogen-activated protein kinase and phospholipase-C␥͞diacyl-glycerol͞Ca 2ϩ ͞PKC pathways (15,18,19).…”
mentioning
confidence: 99%